I hate Fairyland. Volume four, Sadly never after - Young, Skottie (Image Comics, 2018)
As Gert navigates a fairy-tale netherworld with a capital "H," Fairyland's baddies brood and brew to revitalize a rotten ruler. Can Fairyland hope to survive the coming storm when the only people trying to save it are the mastermind tag team of Larry and Duncan Dragon? Are the fates of Gertrude and the land she loves to hate more intertwined than anyone expected?